A study on the defect liability on low cost housing / Mohammad Azlin Hamat - Hamat, Mohammad Azlin (Faculty of Architecture, Planning and Surveying, 2013)
According to a statement issued by the Ministry of Finance Malaysia, the period of defective liability is a period which the contractor must repair any defects identified by supervisors after completion of the work certified. All defect repair expenses shall be borne by the contractor and no additional cost to the Government. Therefore, the aim of this study is to overcome the problems faced by home buyers. This study will make a study of the defects liability period and the reason often given by the contractor in overcoming defects in a building.